Endoplasmic reticulum stress and mitochondrial biogenesis are potential therapeutic targets for abdominal aortic aneurysm. (11th October 2019) - Miyao, Masashi; Cicalese, Stephanie; Cooper, Hannah A.; Eguchi, Satoru
Abstract: Endoplasmic reticulum (ER) and mitochondria are crucial organelles for cell homeostasis and alterations of these organelles have been implicated in cardiovascular disease. However, their roles in abdominal aortic aneurysm (AAA) pathogenesis remain largely unknown. In a recent issue of Clinical Science, Navas-Madronal et al. ((2019), 133 (13), 1421–1438) reported that enhanced ER stress and dysregulation of mitochondrial biogenesis are associated with AAA pathogenesis in humans. The authors also proposed that disruption in oxysterols network such as an elevated concentration of 7-ketocholestyerol in plasma is a causative factor for AAA progression. Their findings highlight new insights into the underlying mechanism of AAA progression through ER stress and dysregulation of mitochondrial biogenesis. Here, we will discuss the background, significance of the study, and future directions.